2007
DOI: 10.1002/mnfr.200700072
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum L.): Adverse effects and drug interactions in humans

Abstract: Garlic (Alllium sativum L., Fam Liliaceae) is used medicinally mainly for the treatment of hypercholesterolemia and prevention of arteriosclerosis. Clinical trials have consistently shown that "garlic breath" and body odor are the most common (and well-documented) complaints associated to garlic intake. Case reports have highlighted the possibility that garlic use may cause allergic reactions (allergic contact dermatitis, generalized urticaria, angiedema, pemphigus, anaphylaxis and photoallergy), alteration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(132 citation statements)
references
References 101 publications
2
120
0
5
Order By: Relevance
“…It is also indicated for decreasing cholesterol and treating arteriosclerosis 12 . However, its anticoagulant effect has been proven in studies that have demonstrated a reduction in platelet activity, leading to hemorrhage 4,13 . This effect may be further heightened by its combined use with allopathic medications, such as acetylsalicylic acid, warfarin and other drugs 12,[14][15] .…”
Section: Garlic (Allium Sativum)mentioning
confidence: 99%
“…It is also indicated for decreasing cholesterol and treating arteriosclerosis 12 . However, its anticoagulant effect has been proven in studies that have demonstrated a reduction in platelet activity, leading to hemorrhage 4,13 . This effect may be further heightened by its combined use with allopathic medications, such as acetylsalicylic acid, warfarin and other drugs 12,[14][15] .…”
Section: Garlic (Allium Sativum)mentioning
confidence: 99%
“…Interactions between garlic and drugs have been well described such as in the case of AIDS medication (e.g. interaction with saquinavir and darunavir metabolism) (Borrelli et al, 2007). Some pieces of evidence underline the ability of OSCs to chemosensitize cancer cells to chemotherapeutic treatment by modulation of cytochrome P450 isoforms.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Cellular damage by oxidation of macromolecules such as DNA, proteins or membrane lipids is an important process during early carcinogenesis (Borrelli et al, 2007;Valko et al, 2006). Antioxidant activities of phytochemicals that counteract ROS or free radicals are therefore highly desirable for potential anti-cancer compounds.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations